2021
DOI: 10.5483/bmbrep.2021.54.1.224
|View full text |Cite
|
Sign up to set email alerts
|

The role of dendritic cells in tumor microenvironments and their uses as therapeutic targets

Abstract: Dendritic cells (DC), which consist of several different subsets, specialize in antigen presentation and are critical for mediating the innate and adaptive immune responses. DC subsets can be classified into conventional, plasmacytoid, and monocyte-derived DC in the tumor microenvironment, and each subset plays a different role. Because of the role of intratumoral DCs in initiating antitumor immune responses with tumor-derived antigen presentation to T cells, DCs have been targeted in the treatment of cancer. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 110 publications
0
32
1
Order By: Relevance
“…The IL-1β/CXCL1/neutrophil axis is documented to drive intestinal mucosal inflammation, activated by ligation of intestinal pattern recognition receptors, including toll-like receptors (TLRs) 31 . In the context of MBI, TLR4 activation is known to drive intestinal toxicity 32 , 33 , however targeting TLR4 directly is challenging due to emerging regulation of tumour response 34 37 . As such, we selected anakinra as our intervention to inhibit inflammatory mechanisms downstream of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…The IL-1β/CXCL1/neutrophil axis is documented to drive intestinal mucosal inflammation, activated by ligation of intestinal pattern recognition receptors, including toll-like receptors (TLRs) 31 . In the context of MBI, TLR4 activation is known to drive intestinal toxicity 32 , 33 , however targeting TLR4 directly is challenging due to emerging regulation of tumour response 34 37 . As such, we selected anakinra as our intervention to inhibit inflammatory mechanisms downstream of TLR4.…”
Section: Discussionmentioning
confidence: 99%
“…Most notably, we observed that tumor tissues of MC38 colon carcinoma in IP6K1 KO mice showed very little CD11c + dendritic cell infiltrate. When dendritic cells sense and present tumor antigens, naive antigen-specific CD4 + and CD8 + T cells are activated, thereby mediating anti-tumor activities (Gardner et al 2020 ; Kim et al 2021 ). Therefore, reduced detection of total and CD8 + killer T cell population in the tumor tissue from IP6K1 KO mice appears the consequence of defective IP6K1 KO dendritic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Dendritic cells (DCs) are major antigen-presenting cells in tumor immune microenvironment and exert anti-cancer activity ( 22 , 23 ). DCs are divided into two principal cell populations, including cDCs and plasmacytoid DCs ( 24 , 25 ). cDCs are subdivided into two subtypes, type 1 cDC (cDC1) and type 2 cDC (cDC2) ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…DCs are divided into two principal cell populations, including cDCs and plasmacytoid DCs ( 24 , 25 ). cDCs are subdivided into two subtypes, type 1 cDC (cDC1) and type 2 cDC (cDC2) ( 23 , 24 ). Both cDC1 and cDC2 had antitumor activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation